2012
DOI: 10.1097/mlr.0b013e318249d6c8
|View full text |Cite
|
Sign up to set email alerts
|

Five-step Methodology for Evaluation and Adaptation of Print Patient Health Information to Meet the <5th Grade Readability Criterion

Abstract: Background In the setting of declining U.S. literacy, new policies include use of clear communication and low literacy accessibility practices with all patients. Reliable methods for adapting health information to meet such criteria remain a pressing need. Objectives To report method validation (Study 1) and method replication (Study 2) procedures and outcomes for a 5-step method for evaluating and adapting print health information to meet the current low literacy criterion of <5th grade readability. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
1
21
0
2
Order By: Relevance
“…Many IPEMs are written well above this recommended level, with more than half being at college level (1). These IPEMs should be written at the average American adult's reading level in hopes of improving patient comprehension (25). Our findings are congruent with readability assessments in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many IPEMs are written well above this recommended level, with more than half being at college level (1). These IPEMs should be written at the average American adult's reading level in hopes of improving patient comprehension (25). Our findings are congruent with readability assessments in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…For example, shortening sentence length (words per sentence) as well as shortening the words themselves (number of syllables per sentence) can increase the comprehensibility of IPEMs (25,27). Other methods of increasing comprehensibility not studied here include use of active voice (25), corresponding higher numerical values to better outcomes (28), creating easy-tounderstand web-page layouts (ie, font) (7), and as well as using adjunct illustrations (29). An inherent limitation to this study is that any visual aids were excluded from the analysis.…”
Section: Improving Ipemsmentioning
confidence: 99%
“…Although the use of readability levels to test for comprehensibility is often recommended in low health literacy interventions (Hill-Briggs, Schumann, & Dike, 2012), research has shown that in cancer communication, readability and comprehensibility are not always related (Friedman & Hoffman-Goetz, 2007). Therefore we primarily chose to pretest the messages extensively for difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Lower literacy has been found to contribute to health disparities, especially among racial and ethnic minorities, specifically in Hispanics and Blacks (Heinrich, 2012; Hill-Briggs, Schumann, & Dike, 2012; Wilson, 2009). …”
Section: Development and Use Of The Brief Copementioning
confidence: 99%
“…Many formulas are available and reliable to test readability including the Flesch–Kincaid Reading Level test, the Flesch Reading Ease, the Simple Measure of Gobbledygook (SMOG), and the Gunning Fog (FOG) Index, though no one measure has been proven to be more accurate than another (Hill-Briggs et al, 2012; Paasche- Orlow et al, 2005). Due to the low literacy rates in the United States, it is recommended that readability levels for health documents, including questionnaires and surveys (Calderon, Morales, Lie, & Hays, 2006), be evaluated prior to distributing among minority populations to ensure they are appropriate for maximum comprehension.…”
Section: Development and Use Of The Brief Copementioning
confidence: 99%